2022
DOI: 10.1177/15357597221101271
|View full text |Cite
|
Sign up to set email alerts
|

Integrating Network Neuroscience Into Epilepsy Care: Progress, Barriers, and Next Steps

Abstract: Drug resistant epilepsy is a disorder involving widespread brain network alterations. Recently, many groups have reported neuroimaging and electrophysiology network analysis techniques to aid medical management, support presurgical planning, and understand postsurgical seizure persistence. While these approaches may supplement standard tests to improve care, they are not yet used clinically or influencing medical or surgical decisions. When will this change? Which approaches have shown the most promise? What a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 52 publications
(51 reference statements)
0
23
0
Order By: Relevance
“…The SOZ and PZ power was not significantly altered in the alpha band [8][9][10][11][12] Hz] (Figure 2B). The SOZ and PZ power was elevated compared to baseline in both beta [13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30] and gamma bands , but post-hoc multiple comparisons revealed that the SOZ elevation in power was only significantly different from non-involved regions in the beta band and only from PZs in the gamma band (Figure 2C-D, beta: SOZ single-population t-test p-value=9.00e-3, one-way ANOVA p-value=2.98e-2, post-hoc pairwise t-test comparison SOZ-Non p-value=2.24e-2; gamma: SOZ single-population t-test p-value=6.70e-3, one-way ANOVA p-value=1.11e-2, post-hoc pairwise t-test comparison SOZ-PZ p-value=1.33e-2).…”
Section: Low Frequency Power Is Attenuated In Sozs When the Network I...mentioning
confidence: 86%
See 3 more Smart Citations
“…The SOZ and PZ power was not significantly altered in the alpha band [8][9][10][11][12] Hz] (Figure 2B). The SOZ and PZ power was elevated compared to baseline in both beta [13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30] and gamma bands , but post-hoc multiple comparisons revealed that the SOZ elevation in power was only significantly different from non-involved regions in the beta band and only from PZs in the gamma band (Figure 2C-D, beta: SOZ single-population t-test p-value=9.00e-3, one-way ANOVA p-value=2.98e-2, post-hoc pairwise t-test comparison SOZ-Non p-value=2.24e-2; gamma: SOZ single-population t-test p-value=6.70e-3, one-way ANOVA p-value=1.11e-2, post-hoc pairwise t-test comparison SOZ-PZ p-value=1.33e-2).…”
Section: Low Frequency Power Is Attenuated In Sozs When the Network I...mentioning
confidence: 86%
“…75,[87][88][89][90][91] Overall, when presumably healthy regions were stimulated, the SOZ theta [4-8 Hz] relative band power was markedly decreased from pre-stimulation baseline. Conversely, SOZ beta [13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30] and gamma relative band power increased when healthy regions were stimulated. Increased inward evoked gamma band power in SOZs is in alignment with previous low-frequency stimulation findings.…”
Section: Does Imbalanced Reciprocal Connectivity Indicate Suppression?mentioning
confidence: 87%
See 2 more Smart Citations
“…Epilepsy has been increasingly identified as a network disorder [11][12][13] . The study of brain connectomics has demonstrated the presence of large-scale network abnormalities even in focal epilepsies [14][15][16] .…”
Section: Introductionmentioning
confidence: 99%